The Role of AI Governance and Digital Accountability in Promoting Inclusive Economic Development in Central Kalimantan - Pratiwi Subianto; Abdul Halim; Tiur Roida Simbolon; Kasi Eselonirmala Waruwu (Journal of International Conference Proceedings, 2026)
Artificial Intelligence (AI) has emerged as a key driver of global economic transformation, offering opportunities for productivity growth, public service efficiency, and regional innovation. However, AI also poses risks of socioeconomic inequality, algorithmic bias, digital exclusion, and weak accountability, challenges particularly pronounced in developing regions like Central Kalimantan. This study analyzes the role of AI Governance and accountability in driving inclusive economic development and formulates a Digital Accountability Framework for Central Kalimantan using a Systematic Literature Review (SLR) with a PRISMA approach. Findings reveal that AI can support inclusive growth through agriculture productivity, forest fire monitoring, targeted public services, and SME strengthening. Without ethical governance, however, AI risks deepening inequality, marginalizing indigenous communities, and creating dependency on nontransparent systems. Therefore, AI Governance must function as institutional development infrastructure. The proposed framework encompasses transparency, fairness, human oversight, data governance, grievance mechanisms, and multistakeholder involvement for inclusive, adaptive, and sustainable development in Central Kalimantan.